[PP.22.17] THE LEFT VENTRICLE DIASTOLIC FUNCTION PROFILE IN PATIENTS WITH ARTERIAL HYPERTENSION AND MILDLY REDUCED KIDNEY FUNCTION. (September 2016) - Torbas, O.; Sirenko, Y.; Radchenko, G.; Rekovets, O.; Kushnir, S.; Granich, V.; Dobrokhod, A.
Abstract : Objective: It has been shown that renal function impairment may potentiate left ventricle stiffening that may influence its diastolic function. So we decided to study it in patients with mildly reduced renal function. Design and method: We examined 52 patients with essential AH stage 2 (mean SBP 158, 04 ± 2, 24 mmHg, mean DBP 92, 19 ± 2, 15 mmHg; eGFR 86, 2 ± 1, 8; age 51, 29 ± 2, 24), 25 men and 27 women. We performed Doppler echocardiography according to local full protocol, LV diastolic function was determined by measuring velocity of the peak E and peak A of transmitral flow with determination of E/A, velocity of peak E' by tissue Doppler with determination of E/E', deceleration time (Dt) and isovolumic relaxation time (IVRT) measurement. eGFR was estimated using CKD-EPI formula. Also we used routine hematology and biochemical blood testing, urine analysis, microalbuminuria and urine creatinine excretion with albumin to creatinine excretion ratio (A/C). To assess the relationship between these values we used Spearman correlation analysis. Results: The mean values were E/A 1, 04 ± 0, 06, E/E' 7, 58 ± 0, 44, Dt 253, 9 ± 12, 6 msec, IVRT 92, 6 ± 3, 9 msec. We found that E/E' was correlated with A/C (r = 0, 38 p = 0, 046), serum sodium (r = 0, 341 p = 0, 038) and with the quantity of leucocytes (Leu) in the urine portion (r = 0, 396 p = 0, 037). E/A was associated with serum potassium (r = -0, 385 p = 0, 035), eGFR (r = 0, 376 p = 0, 017), uric acid (r = -0, 675 p = 0, 005), the quantity of Leu in hematology (r = -0, 436 p = 0, 033) and urine (r = -0, 456 p = 0, 013) samples. Dt was associated with urine specific density (r = 0, 313 p = 0, 039), eGFR (r = 0, 693 p = 0, 034), erythrocyte sedimentation rate (r = 0, 410 p = 0, 046), quantity of Leu (r = 0, 0576 p = 0, 001) and erythrocytes (r = 0, 387 p = 0, 042) in urine portion. IVRT correlated with serum sodium (r = 0, 374 p = 0, 019) and potassium (r = 0, 383 p = 0, 04) concentration, eGFR (r = 0, 412 p = 0, 011) and blood hemoglobin concentration (r = 0, 485 p = 0, 16). Conclusions: In patients with arterial hypertension and started renal function impairment all the predictors found could be useful for the prognosis of the development of LV diastolic dysfunction.